Shared Leadership : the Essential Ingredient for Effective PLCs. - Wilhelm, Terry (SAGE Publications, 2016)
Supercharge your school culture with authentic shared leadership. Why do so many professional learning communities (PLCs) fail? Terry Wilhelm answers this question-and more-by challenging educators to work together once and for all to cultivate shared leadership. Through simple practices and processes, Shared Leadership: The Essential Ingredient for Effective PLCs highlights approaches that spark and sustain a successful PLC. If you need how-to steps to fuel a healthy school culture in curriculum, instruction, and assessment, it's all here: Developing teacher leadership and enhancing collabor.